2023
DOI: 10.1038/s41467-023-36140-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 patients have impaired plasmacytoid dendritic cell-mediated control of SARS-CoV-2

Abstract: Type I and III interferons (IFN-I/λ) are important antiviral mediators against SARS-CoV-2 infection. Here, we demonstrate that plasmacytoid dendritic cells (pDC) are the predominant IFN-I/λ source following their sensing of SARS-CoV-2-infected cells. Mechanistically, this short-range sensing by pDCs requires sustained integrin-mediated cell adhesion with infected cells. In turn, pDCs restrict viral spread by an IFN-I/λ response directed toward SARS-CoV-2-infected cells. This specialized function enables pDCs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…The deconvolution results for Nanostring data (Figure S1f) also show that ROIs labelled as bronchial epithelium and T2 contain a high proportion of epithelial cells. Additionally, we found that COVID‐affected ROIs show a high proportion of plasmacytoid dendritic cells (pDC) and macrophages, suggesting a COVID‐19 induced cytokine storm [20–22]. While CD8 T cells were significantly higher in COVID‐19 samples based on PhenoImager HT data, this difference was not apparent in the GeoMx data (although the median gene expression value for relevant markers was indeed higher in COVID‐19 samples) (Figure S1g–i).…”
Section: Resultsmentioning
confidence: 99%
“…The deconvolution results for Nanostring data (Figure S1f) also show that ROIs labelled as bronchial epithelium and T2 contain a high proportion of epithelial cells. Additionally, we found that COVID‐affected ROIs show a high proportion of plasmacytoid dendritic cells (pDC) and macrophages, suggesting a COVID‐19 induced cytokine storm [20–22]. While CD8 T cells were significantly higher in COVID‐19 samples based on PhenoImager HT data, this difference was not apparent in the GeoMx data (although the median gene expression value for relevant markers was indeed higher in COVID‐19 samples) (Figure S1g–i).…”
Section: Resultsmentioning
confidence: 99%
“…The contact between pDCs and infected cells is beneficial for host defense, considering that HEV is resistant to exogenous IFN treatment (Todt et al, 2016; Wang et al, 2016) . On a different note, a prior study has shown that HEV-ORF3 can attenuate TLR7 expression (Lei et al, 2018) , this effect is less likely to be observed for pDCs as these are non-permissive to most viruses (Reizis, 2019; Silvin et al, 2017; Venet et al, 2023) . pDC response failed to control HEV replication after 18h of co-culture with PLC3 cells but effectively controlled HEV replication in HepG2/C3A under the same conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Information on sex and age was available for all subjects, yet we previously showed that pDC responses are within the same range for all donors (Decembre et al, 2014) . PBMCs were isolated using Ficoll-Hypaque density centrifugation and pDCs were positively selected from PBMCs using BDCA-4-magnetic beads (MACS Miltenyi Biotec), as previously described (Decembre et al, 2014; Dreux et al, 2012; Venet et al, 2023) . The typical yields of PBMCs and pDCs were 500-800×10 6 and 1-2×10 6 cells, respectively, with a typical purity of >95% pDCs.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, studies have found that type I and III IFNs can control SARS-CoV-2 replication in the upper and lower respiratory tracts 54,55 . Further, pDCs and alveolar macrophages have been implicated in modulating inflammation and viral control [56][57][58][59] . We recently determined the importance of the CCR2-monocyte signaling axis in promoting virus control and dissemination within the lungs and mediating protection 18 .…”
Section: Discussionmentioning
confidence: 99%